Novel analyses of long-term data provide a scientific basis for chlorophyll-a thresholds in San Francisco Bay. (15th October 2017) - Sutula, Martha; Kudela, Raphael; Hagy, James D.; Harding, Lawrence W.; Senn, David; Cloern, James E.; Bricker, Suzanne; Berg, Gry Mine; Beck, Marcus
Abstract: San Francisco Bay (SFB), USA, is highly enriched in nitrogen and phosphorus, but has been resistant to the classic symptoms of eutrophication associated with over-production of phytoplankton. Observations in recent years suggest that this resistance may be weakening, shown by: significant increases of chlorophyll- a ( chl-a ) and decreases of dissolved oxygen (DO), common occurrences of phytoplankton taxa that can form Harmful Algal Blooms (HAB), and algal toxins in water and mussels reaching levels of concern. As a result, managers now ask: what levels of chl-a in SFB constitute tipping points of phytoplankton biomass beyond which water quality will become degraded, requiring significant nutrient reductions to avoid impairments? We analyzed data for DO, phytoplankton species composition, chl-a, and algal toxins to derive quantitative relationships between three indicators (HAB abundance, toxin concentrations, DO) and chl-a . Quantile regressions relating HAB abundance and DO to chl-a were significant, indicating SFB is at increased risk of adverse HAB and low DO levels if chl-a continues to increase. Conditional probability analysis (CPA) showed chl-a of 13 mg m −3 as a "protective" threshold below which probabilities for exceeding alert levels for HAB abundance and toxins were reduced. This threshold was similar to chl-a of 13–16 mg m −3 that would meet a SFB-wide 80% saturation Water Quality Criterion (WQC) for DO. Higher "at risk" chl-a thresholds from 25 to 40 mg m −3 corresponded to 0.5 probability of exceeding alert levels for HAB abundance, and for DO below a WQC of 5.0 mg L −1 designated for lower South Bay (LSB) and South Bay (SB). We submit these thresholds as a basis to assess eutrophication status of SFB and to inform nutrient management actions. This approach is transferrable to other estuaries to derive chl-a thresholds protective against eutrophication. Highlights: Water-quality impairments rarely occur in San Francisco Bay despite high nutrients. chl- a thresholds were derived to protect the Bay from future impairments. HAB abundance and DO were significantly correlated with chl-a. chl-a thresholds based on HAB and DO impairments converged on similar values. The Bay may reach c hl-a thresholds if phytoplankton assimilate available nutrients.